Human rights and law : bonded labour in India / Ramesh Kumar Tiwari. - Tiwari, R. K. (Ramesh Kumar) (Foundation Books, 2011)
Human Rights and Law: Bonded Labour in India deals with the problem of debt bondage and the way it has been treated during the British as well as in the post-independence period. Analysis has been made of the motivations for carrying out the reform; the processes involved in formulating the legislation, contributions by different agencies, discussion in the parliament, etc. The two legislations: the Indian Slavery Act, 1843 and bonded labour system (Abolition) Act, 1976 provide a comparative perspective in the making of social legislation in two different historical settings and different political systems.